2018
DOI: 10.4103/ccd.ccd_60_18
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of pH and chlorine content of a novel herbal sodium hypochlorite for root canal disinfection: An experimental In vitro study

Abstract: Introduction:Sodium hypochlorite (NaOCl) is widely used endodontic irrigant with its array of advantages and disadvantages. Addition of herbal agents to NaOCl might help in enhancing its efficacy.Materials and Methods:NaOCl was prepared using chlorinated lime, anhydrous sodium carbonate, and distilled water to obtain 6% fresh solution. Then, this solution was evaluated for its pH and chlorine content. The fresh herbal extract of Cymbopogon citratus (lemongrass), Mentha piperita (peppermint), and Ocimum sanctum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 28 publications
0
1
0
Order By: Relevance
“…Pradhan MS et al [54] aimed to make an herbal sodium hypochlorite solution by combining 6% sodium hypochlorite with 10% extracts of three herbal species (C. citarus, M. piperita, and O. sanctum). The authors hypothesized that the simultaneous antibacterial effect of this mixture might be achieved without sacrificing pH or chlorine levels.…”
Section: Herbal Remedies and Endodontic Treatmentsmentioning
confidence: 99%
“…Pradhan MS et al [54] aimed to make an herbal sodium hypochlorite solution by combining 6% sodium hypochlorite with 10% extracts of three herbal species (C. citarus, M. piperita, and O. sanctum). The authors hypothesized that the simultaneous antibacterial effect of this mixture might be achieved without sacrificing pH or chlorine levels.…”
Section: Herbal Remedies and Endodontic Treatmentsmentioning
confidence: 99%
“…But since the outbreak of the pandemic, its use has amplified unmeasurably. It is reported that halogenated volatile organic compounds (VOCs) such as chloroform and carbon tetrachloride present indoors possibly arise from the reaction of HOCl with organic surfactant compounds [54][55][56][57][58][59][60].…”
Section: Effect Of Sodium Hypochlorite (Naocl) In Atmospherementioning
confidence: 99%
“…pH can influence many of the properties of the root canal irrigant. such as antibacterial efficacy and shelf life [23][24][25][26] , as well as cytotoxicity 27 , NaOCl tissue dissolving ability 28 , and EDTA smear layer removal and chelating ability 29 .…”
Section: Introductionmentioning
confidence: 99%